Advocating for HIV Prevention and Care: A Critical Role for Older Women Living With HIV in Rural Kenya. (15th April 2014) - Kako, Peninnah M.; Kibicho, Jennifer W.; Mkandawire-Valhmu, Lucy; Stevens, Patricia E.; Karani, Anne K.
The number of older women living with HIV in Kenya is increasing. However, there are little empirical data available about their role in HIV prevention. The purpose of this study was to understand the nuanced role of older women in HIV prevention. We engaged 54 HIV-positive women in three narrative-eliciting interviews between 2009 and 2010 over a period of 6 months to understand their role in HIV prevention. In this article, we focus on a sample subset of 7 rural women 50 years and older living with HIV. From narrative analysis of 19 interviews from 7 women who were 50 years and older, four themes emerged: promoting HIV transmission risk reduction, promoting HIV testing, educating others about HIV, and protecting children from HIV infection. HIV-positive older women are engaged in helping mitigate HIV in their communities and should be central to meaningful HIV-related interventions especially in rural communities